Extracorporeal Shock Wave Lithotripsy for Large Common Bile Duct and Pancreatic Duct Stones: Efficacy, Safety and Analysis of Factors That Favor Stone Fragmentation - Khan, Mushtaq Ahmad; Wani, Zaffar Ali; Dar, Hilal Ahmad; Shah, Altaf H; Singh, Bhagat; Javid, Gul (Journal of Digestive Endoscopy, 2019)
Background: Extracorporeal shockwave lithotripsy (ESWL) with subsequent endoscopic extraction of residual fragments is an established treatment option in technically challenging situations for extraction of pancreatic and common bile duct calculi. Common bile duct (CBD) stone fragmentation rates of 71 to 95% have been reported with ESWL, leading to final duct clearance rates of 70 to 90%. While complete clearance of 76% and partial clearance of 17% of pancreatic duct calculi have been documented with ESWL, our study was undertaken to investigate the efficacy and safety of ESWL in clearance of difficult bile duct and large pancreatic duct calculi.Methods: The study population consisted of 61 patients who had either large or difficult bile duct calculi or large pancreatic duct calculi documented on ultrasonography abdomen or magnetic resonance cholangiopancreatography (MRCP). All patients were subjected to ESWL sessions with endoscopic nasobiliary drainage (ENBD) placement till stones got fragmented.Results: A total of 1,284 patients underwent ERCP for either choledocholithiasis or pancreatic duct calculi during the study period (June 2015 to December 2016). Out of them 61 patients had either large or difficult CBD calculi or large pancreatic duct calculi. Forty (65.57%) had choledocholithiasis (Group-A) and 21 (34.42%) had chronic calcific pancreatitis (Group-B). CBD was cleared in 37 patients (92.5%) and 3 patients (7.5%) underwent surgical intervention. Main pancreatic duct (MPD) was cleared in all patients with clearance rate of 100%.Conclusions: ESWL is an effective and safe method for clearance of difficult CBD and pancreatic duct calculi. Combined efficacy of duct clearance is >90%. Complications are minimal and managed conservatively.
Keywords: Common bile duct; Extracorporeal shock wave lithotripsy; Main pancreatic duct